Porous Organic Compounds – Small Pores on the Rise. Issue 43 (20th October 2021) - Kunde, Tom; Pausch, Tobias; Schmidt, Bernd M.
Abstract: Porous materials are important for various energy‐related technologies such as catalysis and separation. While porous organic cage compounds are a rather recent addition to the field of porous materials, these discrete nanocavities have since emerged as a versatile functional‐materials platform, facilitated by the solubility of the materials in common organic solvents. In contrast to other frameworks, organic cages are assembled first from modular building blocks in solution and then packed in the solid‐state in a next step. In this minireview, we highlight examples of porous organic cages with focus on how the intrinsic nanopore can be controlled and utilized, especially focusing on their synthesis and the gas sorption properties of smaller intrinsic pores of porous organic cage compounds, porous macrocycles, and other related compounds. Abstract : Make small great again . This Minireview focuses on smaller porous organic cages and other porous organic compounds, such as trianglimines and cyclobenzoins. Control over the intrinsic nanopore by organic synthesis and the gas sorption properties of smaller intrinsic pores showcase why size does matter and why small is the new big.